Digital Twin for FANUC Robots: Industrial Robot Programming and Simulation Using Virtual Reality - Garg, Gaurav; Kuts, Vladimir; Anbarjafari, Gholamreza (MDPI, 2021)
A Digital Twin is the concept of creating a digital replica of physical models (such as a robot). This is similar to establishing a simulation using a robot operating system (ROS) or other industrial-owned platforms to simulate robot operations and sending the details to the robot controller. In this paper, we propose a Digital Twin model that assists in the online/remote programming of a robotic cell by creating a 3D digital environment of a real-world configuration. Our Digital Twin model consists of two components, (1) a physical model: FANUC robot (M-10iA/12), and (2) a digital model: Unity (a gaming platform) that comes with specialized plugins for virtual and augmented reality devices. One of the main challenges in the existing approach of robot programming is writing and modifying code for a robot trajectory that is eased in our framework using a Digital Twin. Using a Digital Twin setup along with Virtual Reality, we observe the trajectory replication between digital and physical robots. The simulation analysis provided a latency of approximately 40 ms with an error range of -0.28 to 0.28 circle across the robot joint movements in a simulation environment and -0.3 to 0.3 circle across the actual robot joint movements. Therefore, we can conclude that our developed model is suitable for industrial applications.
Keywords: Digital Twin; robot programming; Virtual Reality; FANUC; Science & Technology - Other Topics; Environmental Sciences & Ecology